Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Kerja dan Pemberian Reward Achievement Kerja terhadap Kinerja Karyawan pada Pt Grab Teknologi Indonesia Provinsi Jawa Barat - Reza Faizal Anshori; Yusi Afriani (Departement of Mathematics Education, 2023)
People are a company's most important asset, carrying out policies and operational activities. The employees with high performance will be the driving force to achieve company goals. The performance of employees must be monitored so that they are skilled and responsible for the tasks assigned. The leadership style is believed to be one of the factors that affects employee performance. The leadership style is thought to be one of the factors that influence employee performance. An unpopular leadership style will result in lower employee performance. Other factors include work motivation, where providing motivation can inspire enthusiasm for producing better work. Another is rewarding achievement, which encourages employees to be more positive in their work and boosts their performance. This study aims to test and analyze the effects of leadership style, work motivation, and reward achievement on employee performance at PT Grab Teknologi Indonesia in West Java Province. The research method uses descriptive and verifiable techniques, collecting data through the distribution of questionnaires. The study found that leadership style, motivation, and reward achievement are significant factors affecting employee performance by 49.2%.